TERAPI AFEKTIF MEDIA DIGITAL TERHADAP PROKRASTINASI AKADEMIK PADA TUGAS AKHIR DAN SKRIPSI MAHASISWA DI ERA PANDEMI COVID-19 - Fani Juliyanto Perdana; Abas Hidayat; Varidlo Fuad (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
ABSTRACTThis study aims to determine the effect of using digital media affective therapy on self-control, self-esteem, and self-efficacy on academic procrastination by students when carrying out their final project or thesis in the era of pandemic COVID-19. This research is an experimental study using a quasi-experimental design. The research population is all active students in the Faculty of UAD IAIN Syekh Nurjati Cirebon who are currently compiling scientific papers in the form of final projects and thesis with a total of 320 students. The sample in this study was taken by simple random sampling, namely two classes which were divided into an experimental group of 160 students and a control group of 160 students. The results showed that students who were carrying out their final project and thesis assisted by the use of digital media affective therapy were proven to have a partially significant effect on self-control (0.000), self-esteem (0.000), and self-efficacy (0.032). from the results of hypothesis testing conducted with the Mann Whitney test with a significant level of 5% on academic procrastination in the era pandemic covid-19.Â Keywords: digital media affective therapy; self-control; self-esteem; self-efficacy; academic procrastination